Semantic shift functional architecture - O. Y. Pavlova (Ukrainian Cultural Studies, 2018)
The article is devoted to the analysis of the functional architecture signification mode. The distinction between functional architecture and symbolic one is determined on the basis of Hegelian approach. This shift generates not only another way of organizing signifiers, but the emergence of a fundamentally different way of relations with the signified, which actually forms a marked semantic shift. Using strategies of semantic analysis to the material of G. Hegel’s aesthetics allows not only expand the horizons of applied semantics, but also understand the patterns of formation of art and aesthetic process in general. In our opinion, G. Child’s definition of monumental architecture as a criterion for the emergence of civilization (in the evolutionary sense of the term), requires Hegelian refinement concerning classic architecture. In the latter one, in comparison with the symbolic one, the following semantic shift is carried out: organization of syndicators already has a greater degree of freedom in it (even before the cultivation of the forms construction), and therefore their artistic transformation becomes possible. Also, the classic culture has a referent, and therefore it has a significant implementation structure. The measure of differentiation of the symbolic value and utilitarian one shows the possibility of its seniority in the logic of cultural development. Exchange measurements of buildings become possible only in the era of a high degree of cultural differentiation in general (and therefore the architecture remains in the conditions of redistribution, and not just as an exchange of goods). Also, for a long time it remained the subject of "demonstrative consumption". Consequently, functional architecture is the result of complex cultural synthesis, in contrast to the syncretism of the symbolic architecture cultural practice. Their organizational separation marks an important semantic shift that we have been trying to describe. In particular, the construction of the Egyptian pyramids of the Ancient kingdom as burial chambers testifies to the cessation of the existence of its own symbolic architecture, according to G. Hegel. It is in the aesthetic analysis of the differences in symbolic architecture that this classic of philosophical thought departs from the speculative nature of its absolute idealism and understanding of art as the first stage of an absolute spirit, as well as it opens the methodological perspectives of semantic analysis.